Pharmaceutical Evaluation of Honokiol and Magnolol on Apoptosis and Migration Inhibition in Human Bladder Cancer Cells - Hisao-Hsien Wang; Ying Chen; Chih-Ying Changchien; Chih-Ying Changchien; Hsin-Han Chang; Pei-Jyun Lu; Heidi Mariadas; Yu-Chen Cheng; Sheng-Tang Wu; Sheng-Tang Wu (Frontiers Media S.A., 2020)
Among herbal medicines, magnolia bark extract, particularly its components honokiol (Hono) and magnolol (Mag), has been widely documented to have antineoplastic properties. The present study aimed to evaluate the synergism of Hono and Mag in bladder cancer therapy both in vitro and in vivo. Treatment with Mag alone at concentrations up to 80 μM failed to have an antiproliferative effect. In contrast, the combination of Hono and Mag at 40 μM decreased viability, caused cell cycle arrest and enhanced the proportion of Annexin V/7AAD-positive cells. Moreover, Mag with Hono at 40 μM induced caspase 3-dependent apoptosis and autophagy. Neither Hono nor Mag alone had an anti-migratory effect on bladder cancer cells. In contrast, Hono and Mag at 20 μM inhibited the motility of TSGH8301 and T24 cells in wound-healing and Transwell assays. The above phenomena were further confirmed by decreased phosphorylated focal adhesion kinase (p-FAK), p-paxillin, integrin β1, and integrin β3 protein levels. In a nude mouse xenograft model, Mag/Hono administration preferentially retarded T24 tumor progression, which was consistent with the results of cellular experiments. Current findings suggest Hono and Mag treatment as a potential anticancer therapy for both low- and high-grade urothelial carcinoma.